If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (13) + -1(x + 1) = 2(3x + -1) 13 + -1(x + 1) = 2(3x + -1) Reorder the terms: 13 + -1(1 + x) = 2(3x + -1) 13 + (1 * -1 + x * -1) = 2(3x + -1) 13 + (-1 + -1x) = 2(3x + -1) Combine like terms: 13 + -1 = 12 12 + -1x = 2(3x + -1) Reorder the terms: 12 + -1x = 2(-1 + 3x) 12 + -1x = (-1 * 2 + 3x * 2) 12 + -1x = (-2 + 6x) Solving 12 + -1x = -2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 12 + -1x + -6x = -2 + 6x + -6x Combine like terms: -1x + -6x = -7x 12 + -7x = -2 + 6x + -6x Combine like terms: 6x + -6x = 0 12 + -7x = -2 + 0 12 + -7x = -2 Add '-12' to each side of the equation. 12 + -12 + -7x = -2 + -12 Combine like terms: 12 + -12 = 0 0 + -7x = -2 + -12 -7x = -2 + -12 Combine like terms: -2 + -12 = -14 -7x = -14 Divide each side by '-7'. x = 2 Simplifying x = 2
| 3(4x-6)-(x-2)= | | 4(n+3)=5(n-3) | | 4-(3x+2)=7x-2(4x-3) | | 3+5(4+2)= | | 6-3+5=3+5 | | 3x-22=2+3 | | -22+8x-4x=30 | | 5x+3-2x=7-4x+1 | | 4/x^6y^6*4x/y^4 | | 2.5x-13=2 | | 2e(x+2)=5 | | u^2+3u+uv+3v=0 | | X-12+x=38 | | X-13=6+2x | | 3x+7=9x-2 | | 4x-21=7 | | -5-21= | | 20x+6=4x-9 | | -5(3y-9)-y=-4(y-4) | | 5(5X+2)-6=25X+4 | | 6[3y-2(y-1)]-2+7=0 | | 2x+29-8x=5 | | x/6-7=-5 | | 4x-8y-9x-7y= | | -6.362-0.9n=0.9(2.3-0.8n)+2.3n | | 4X-6=4(X-1) | | -2x(x-1)+5x=2(2x-1) | | Y3/4x+7 | | log(x+1)=5.8 | | -9(k+9)-8= | | 24+-5y+5*24+-5y+11=35 | | 12+1/3y=-1 |